2012
DOI: 10.1111/j.2042-3292.2011.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a point‐of‐care test for measurement of blood triglyceride levels for rapid detection of equid hypertriglyceridaemia

Abstract: Summary This project investigated the clinical value of a human whole blood point‐of‐care (POC) triglyceride (TG) measurement device to determine equid blood TG concentrations. Equid plasma TG measurements were determined in a commercial laboratory and also using whole blood and plasma on the POC device from equid patients with TG concentrations from within the normal range to severely hypertriglyceridaemic. Results were compared between methods using the Bland‐Altman method for validation. Seventy‐four sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Assessment of method agreement revealed that the POC analyzer systemically overestimated triglyceride concentrations when compared to a standard laboratory assay. This finding was in concordance with the results of previous studies in dogs, cats, and horses . Disagreement appeared to be more pronounced in horses and ponies compared to donkeys, and the absolute disagreement between methods increased with rising triglyceride concentrations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Assessment of method agreement revealed that the POC analyzer systemically overestimated triglyceride concentrations when compared to a standard laboratory assay. This finding was in concordance with the results of previous studies in dogs, cats, and horses . Disagreement appeared to be more pronounced in horses and ponies compared to donkeys, and the absolute disagreement between methods increased with rising triglyceride concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Assuming that the POC analyzer is calibrated by default for use with capillary blood, this could explain why it overestimates (in comparison with a standard assay designed for use with jugular venous blood) triglyceride concentrations when used with jugular venous blood. In fact, in the other studies in which similar disagreement between the POC analyzer and the standard laboratory assay was detected, analyses were also performed using native or anticoagulated jugular venous blood . Conversely, in a human study utilizing whole capillary blood samples, mean bias between the POC analyzer and a standard laboratory assay was low at <1% .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Hyperlipemia can be suspected based on clinical signs, plasma, or serum turbidity but is confirmed by measuring serum triglyceride concentrations. There are point-of-care sensitive triglyceride analyzers available in the market [14], which could be recommendable for farms with large number of donkeys. Clinicians should also know that because the upper reference limit for triglyceride concentrations (248 mg/dL) is higher in healthy donkeys than horses and ponies [15], the accepted definitions for hypertriglyceridemia (<500 mg/dL) and lipemia/hyperlipemia (>500 mg/dL) in horses and ponies may not be suitable for donkeys.…”
Section: Dyslipidemiasmentioning
confidence: 99%